Karaya gum electrocardiographic electrodes for preterm infants. Issue 12 (December 1987) - Cartlidge, P H; Rutter, N
Abstract : Changes in transepidermal water loss were used to measure skin damage caused by removal of electrocardiograph electrodes in 20 preterm infants. Electrodes secured by conventional adhesive damaged the skin, leading to a potentially dangerous increase in skin permeability. In contrast, those secured by karaya gum caused no skin damage.